Prevalence and risk factors for disrupted circadian rhythmicity in children with optic nerve hypoplasia. Issue 10 (24th June 2010) - Rivkees, S A; Fink, C; Nelson, M; Borchert, M
Abstract : Background/aims: Children with optic nerve hypoplasia (ONH) have visual impairment and may have hypopituitarism and developmental delay. Children with ONH have also been reported to have abnormal sleep–wake cycles. We assessed the incidence and nature of sleep–wake abnormalities in children with ONH. Methods: Rest–activity patterns were assessed in 23 children with ONH using actigraphy, which is a non-invasive method for continuously monitoring activity. The children also had formal assessment of pituitary function, visual acuity measurements, assessment of papillary responsiveness, MRI scans of the head and assessment of neurocognitive function. Results: Sufficient actigraphy data were obtained on 19 of the children. Analysis of expressed rhythmicity revealed normal rest–activity patterns in 13 children (68%). Of the six children (32%) with abnormal rhythmicity, three had fragmented sleep, one had free-running rest–activity cycles and two were arrhythmic. Of the children with normal rhythmicity, the following were found: hypoplastic corpus callosum in 30%, growth hormone deficiency in 53%, hypothyroidism in 23%, adrenal insufficiency in 30%, diabetes insipidus in 0% and developmental delay in 15%. Of the children with abnormal rhythmicity, the following were found: hypoplastic corpus callosum in 66% (p>0.05), severe visual impairment in 100% (p=0.006), abnormal pupillary responsiveness in 85% (p=0.0084), cognitive impairment in 100% (p=0.04) and multiple hormonal deficiencies in 66% (p=0.03). Conclusions: Abnormal rest–activity rhythmicity patterns are present in 30% of children with ONH. The best predictors of abnormal rhythmicity are severe vision impairment, abnormal pupillary responsiveness, developmental delay and multiple hormonal deficiencies.